Resveratrol Reverses Retinoic Acid Resistance of Anaplastic Thyroid Cancer Cells via Demethylating CRABP2 Gene - Liu, Xin; Li, Hong; Wu, Mo-Li; Wu, Jiao; Sun, Yuan; Zhang, Kai-Li; Liu, Jia (Frontiers in Endocrinology, 2019)
Abstract: Background: Cellular retinoic acid binding protein 2 (CRABP2) mediates retinoic acid/RA anti-cancer pathway. Resveratrol effectively reverses RA tolerance and up-regulates CRABP2 expression of anaplastic thyroid cancer cell line THJ-11T. Because DNA methylation is responsible for CRABP2 silencing, CRABP2 methylation status of THJ-11T cells and demethylating effect of resveratrol on this gene are elucidated. Materials and methods: The statuses of CRABP2 expression and methylation and the levels of DNA methyltransferases(DNMTs) DNMT1, DNMT3A, and DNMT3B of THJ-11T cells were examined before and after resveratrol treatment via multiple experimental methods. Human medulloblastoma UW228-2 cell line was cited as the positive control of CRABP2 methylation and gemcitabine as the demethylator control. Results: RT-PCR, immunocytochemical staining and Western blotting showed that resveratrol significantly increased CRABP2 expression and RA sensitivity of THJ-11T and UW228-2 cells. Bisulfite sequencing showed 5 CpG methylation sites at CRABP2 promoter region of both cell lines, which were partially (3/5) demethylated by resveratrol and totally (5/5) by gemcitabine. DNMT1, DNMT3A, and DNMT3B were reduced in UW228-2 cells and DNMT1 and DNMT3A were reduced in THJ-11T cells after resveratrol treament in time-related fashion. Conclusion: Resveratrol is able to erase CRABP2 methylation and thereby increased RA sensitivity of THJ-11T and UW228-2 cells. This study demonstrates the additional value of the natural polyphenolic compound resveratrol as a demethylator in cancer treatments.